Improved broad-spectrum antibiotics against Gram-negative pathogens via darobactin biosynthetic pathway engineering. Issue 35 (12th August 2021) - Groß, Sebastian; Panter, Fabian; Pogorevc, Domen; Seyfert, Carsten E.; Deckarm, Selina; Bader, Chantal D.; Herrmann, Jennifer; Müller, Rolf
Abstract : Heterologous expression of a synthetically engineered darobactin gene cluster in E. coli yields new darobactin derivatives with improved anti-Gram-negative activity. Targeted gene deletions provide first insights into biosynthetic steps. Abstract : The development of new antibiotics is imperative to fight increasing mortality rates connected to infections caused by multidrug-resistant (MDR) bacteria. In this context, Gram-negative pathogens listed in the WHO priority list are particularly problematic. Darobactin is a ribosomally produced and post-translationally modified bicyclic heptapeptide antibiotic selectively killing Gram-negative bacteria by targeting the outer membrane protein BamA. The native darobactin A producer Photorhabdus khanii HGB1456 shows very limited production under laboratory cultivation conditions. Herein, we present the design and heterologous expression of a synthetically engineered darobactin biosynthetic gene cluster (BGC) in Escherichia coli to reach an average darobactin A production titre of 13.4 mg L −1 . Rational design of darA variants, encoding the darobactin precursor peptide with altered core sequences, resulted in the production of 13 new 'non-natural' darobactin derivatives and 4 previously hypothetical natural darobactins. One of the non-natural compounds, darobactin 9, was more potent than darobactin A, and showed significantly improved activity especially against Pseudomonas aeruginosa (0.125 μg mL −1 ) and Acinetobacter baumannii (1–2 μg mL −1 ). Importantly, it also displayed superior activity against MDR clinical isolates of E . coli (1–2 μg mL −1 ) and Klebsiella pneumoniae (1–4 μg mL −1 ). Independent deletions of genes from the darobactin BGC showed that only darA and darE, encoding a radical forming S -adenosyl-l -methionine-dependent enzyme, are required for darobactin formation. Co-expression of two additional genes associated with the BGCs in hypothetical producer strains identified a proteolytic detoxification mechanism as a potential self-resistance strategy in native producers. Taken together, we describe a versatile heterologous darobactin platform allowing the production of unprecedented active derivatives in good yields, and we provide first experimental evidence for darobactin biosynthesis processes.